Fluorescence-based optical biosensors for clinical and environmental applications - Psoma, Sotiria D. (Cranfield University, 1996)
The aim of this thesis was to investigate the feasibility of simultaneous utilisation of pH and oxygen-dependent fluorescent indicators for the development of a novel fibre-optical fluorescence-based bio sensor. This approach would be used to measure simultaneously changes in the two indicator species generated by a single enzyme-catalysed reaction in response to one analyte where both the indicators and the enzyme are immobilised in the same sol-gel matrix, and to offer more accurate and reliable results using this portable optical biosensor in the clinical and environmental fields. HPTS (1-hydroxypyrene-3,6,8-trisulfonic acid) and tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate, respectively, were used as the target fluorescent indicators; these two indicators had no cross sensitivity separate or in the same solution and well-separated emission bands at 510 nm and 610 mn, respectively. The catalytic oxidation of glucose by the enzyme glucose oxidase was initially investigated using the two indicators, and subsequently the same principle was applied in other biocatalysed oxidations such as of lactate, xanthine and phenol. Substrate concentration was assessed by simultaneously measuring two parameters: oxygen consumption, through the reduction of the fluorescence intensity of tris(2,2'-bipyridyl) ruthenium(II) chloride hexahydrate; and the production of acid, through pH changes affecting the fluorescence intensity of HPTS.A thorough spectroscopic study of the enzymatic oxidation of glucose was performed using glucose oxidase in solution in a cuvette, in the presence of both indicators. A number of combinations of wavelengths of the indicators for excitation and fluorescence were utilised in order to establish calibration curves with the optimum performance for glucose detection in the diabetic range. Similarly results were taken from the kinetic studies of lactate oxidase, xanthine oxidase and polyphenol oxidase for the detection of lactate and xanthine in blood and phenol in water at ppb-levels, using the above principle. The application and characterisation of immobilisation techniques for the fluorescence-based blood-glucose b iosenor were carried out. The advantages of the microcapsulation sol-gel method over conventional immobilisation techniques for application in an optical biosensor, were elucidated and this immobilisation technique was implemented for glucose and phenol detection. Finally, additional solution studies were conducted and used to evaluate the implementation and performance of the above method when used for the detection and measurement of glucose concentration in biological samples such as human serum.